2018
DOI: 10.1177/1934578x1801301033
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Phytotoxic Activity of Rosmarinus officinalis Essential Oil

Abstract: In this study we determined the chemical composition of R. officinalis essential oil and evaluated its possible phytotoxic activity. The chemical composition of the essential oil was studied by GC and GC-MS analyses. A total of 57 compounds were identified and the main components are α-pinene (24.9%), verbenol (8.5%), verbenone (8.5%), 1,8-cineol (8.2%) and isoborneol (8.1%). Moreover, the essential oil and its main constituents, α-pinene and 1,8-cineol,were evaluated for their possible in vitro phytotoxic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…E. gunnii EO showed no phytotoxic activity on the tested seed (data not shown). Its principal component, 1,8 cineole, was inactive against several of the tested seeds, as shown in our previous studies (Caputo et al, 2018).…”
Section: Phytotoxic Activitysupporting
confidence: 84%
“…E. gunnii EO showed no phytotoxic activity on the tested seed (data not shown). Its principal component, 1,8 cineole, was inactive against several of the tested seeds, as shown in our previous studies (Caputo et al, 2018).…”
Section: Phytotoxic Activitysupporting
confidence: 84%
“…According to Shao et al, [ 65 ], the 1,8-cineole compound obtained lower results for the inhibition of the root growth of Amaranthus retroflexus and Poa annua , when compared to the other two major constituents of the Seriphidium terrae-albae essential oil (α-thujone and β-thujone). Other authors also demonstrate the phytotoxic potential of 1,8-cineole on different species of receptor plants [ 66 , 67 , 68 ]; in addition, compounds such as δ-cadinene and ( E )-Caryophyllene have also shown phytotoxic potential on several plant species; in addition, other compounds such as δ-cadinene and ( E )-Caryophyllene have also shown phytotoxic potential on several plant species such as Mimosa pudica , Senna obtusifolia , Sinapis arvensis , Trifolium campestre , and Phalaris canariensis weeds [ 58 , 69 ], results similar to those of other authors [ 63 , 70 ]. Jaradat [ 71 ] points out that the Teucrium polium L. essential oil has α-cadinol as the component with the highest content (46.80%).…”
Section: Resultsmentioning
confidence: 96%
“…The highest values for the isoborneol content were obtained in the mid-and post-flowering stage. Isoborneol content in the previous studies was found different, such as 3.48 % (Martínez et al, 2009), 0.20% (Hussain et al, 2010), 5.68% (Asressu and Tesema, 2014), 2.28%-9.8% (Farhat et al, 2017), 6.04%-12.02% (Gürbüz et al, 2017), 8.10% (Caputo et al, 2018), 11.96%-14.89% (Yıldırım, 2018), 0.11% (Micić et al, 2021), 6.00% (Khanjani et al, 2021), 30.29% (Xylia et al, 2021).…”
Section: Chemical Composition Of Essential Oilmentioning
confidence: 91%